Outsourcing corporate heritage marketing in the omnichannel context: a process perspective of a small winery - Pier Franco Luigi Fraboni; Andrea Sabatini; Valerio Temperini (Il capitale culturale, 2023)
The pandemic crisis and the disruptive impact of digitalisation have led firms to undertake the omnichannel continuum to meet new customers’ needs for a seamless purchasing experience. A frictionless customer journey requires coherent marketing initiatives across channels. Small firms, which usually lack human and financial resources, are approaching the omnichannel paradigm through outsourcing. As a result, small businesses that recognise the importance of corporate heritage marketing (CHM) in their overall marketing strategies face challenges in maintaining the consistency of CHM initiatives across their partners’ channels. Hence, the present study proposes a case study methodology to unfold how small firms develop consistent CHM initiatives in the omnichannel partners’ channels. The findings suggest that small companies should open their CHM process to omnichannel partners to develop consistent CHM initiatives among partners’ channels.   La digitalizzazione e la crisi pandemica hanno indotto numerose aziende ad intraprendere il continuum omnicanale per soddisfare le nuove esigenze dei clienti. Predisporre percorsi di acquisto fluidi, integrati e sinergici implica lo sviluppo di iniziative di marketing coerenti tra i vari canali. Le piccole imprese, che solitamente non dispongono di adeguate risorse umane e finanziarie, ricorrono all’outsourcing per approcciarsi a tale paradigma. Di conseguenza, le piccole realtà che riconoscono al proprio corporate heritage marketing (CHM) un ruolo di primo piano, si ritrovano di fronte alla sfida di mantenere la coerenza delle proprie iniziative di CHM anche nei canali dei loro partner omnicanale. Il presente studio si propone di approfondire la suddetta tematica attraverso la metodologia dello studio di caso. I risultati evidenziano che le piccole imprese dovrebbero aprire il loro processo di CHM ai partner omnicanale per sviluppare iniziative di CHM coerenti anche nei loro canali.